Does technology matter for combating economic and financial crime? A panel data study - Achim, Monica Violeta; Borlea, Sorin Nicolae; Văidean, Viorela Ligia (Technological and Economic Development of Economy, 2021)
In this paper we analyze the influence of technology on the level of the economic and financial crime, using data for 185 countries over the 2012–2015 time period and controlling for many important variables. First, we find that on average, the size of the economic and financial crime in low income countries is about double compared to that of high income countries, while their Research and development expenditure (as % of GDP) are about four times lower than in high income countries. We find clear evidence that increased technology reduces the size of the economic and financial crime. In addition, we find that Research and development expenditure (% of GDP) matter more in reducing the economic and financial crime in low income countries than they do in high income countries. Our main findings are generally stable after conducting some robustness checks. From a policy perspective, our study may prove to be of great use to decision makers of the states, to government and non-governmental enterprises and to potential investors within different markets.First published online 6 January 2021